Extinction rates of the Meade Basin rodents: application to current biodiversity losses. (9th November 2016) - Martin, Robert A.; Peláez‐Campomanes, Pablo
Abstract : Extinction rates for terrestrial rodent species from palaeontological sites in the Meade Basin of southwestern Kansas and an archaeological site in New Mexico are compared with extinction rates for modern rodents from locations affected by anthropogenic activities. Background extinction rates are defined as global extinctions occurring over proscribed intervals in the absence of significant environmental perturbations. Background rates for the Meade Basin are estimated at 0– 1.0 E/MSY (extinctions per million species years). Elevated rates from 1.4 to 6.25 E/MSY are associated with volcanic events and Late Pleistocene environmental change. These rates are considerably less than those for rodent extinction rates promoted by human activities during the Holocene, the latter ranging from 42.3 to 50, 000 E/MSY.